Effect of Down-Regulated Transcriptional Repressor ZEB1 on the Epithelial-Mesenchymal Transition of Ovarian Cancer Cells. Issue 8 (1st October 2013) - Chen, Dengyu; Wang, Jing; Zhang, Yunxia; Chen, Junsong; Yang, Cuiping; Cao, Wenhu; Zhang, Hongyi; Liu, Yurong; Dou, Jun
Abstract : Background: Progress has been made against early events of malignant transformation and drug resistance associated with epithelial ovarian cancer; uncontrolled metastases, however, still accounts for most patient deaths. The molecular mechanism that regulates the process of epithelial ovarian cancer metastases is not yet clearly understood. The purpose of this study was to investigate the effect of down-regulating the transcriptional repressor zinc-finger E-box–binding homeobox 1 (ZEB1) on an epithelial-mesenchymal transition (EMT) of human ovarian cancer SKOV3 cell line in vitro and in vivo. Methods: The human ovarian cancer cells SKOV3 and HO8910 were transfected with an expression vector-based small hairpin RNA (shRNA) targeting ZEB1 (shZEB1), and the stably transfected cells were selected. Colony-forming, wound-healing, and cellular migration assays were respectively used. The tumorigenicity of shZEB1-SKOV3 was also evaluated in mice. Results: The shZEB1-SKOV3 and shZEB1-HO8910 cells showed a lower level of ZEB1 expression and weaker cell migration than the control cells. Moreover, down-regulating ZEB1 expression with shRNA in the cells enhanced the expression of miR-200c that acted as a tumor suppressor to inhibit the epithelial-mesenchymal transition of shZEB1-SKOV3 cells and to block shZEB1-SKOV3 cell metastasis in vivo. The shRNA-mediated down-regulation ZEB1 in SKOV3 cells significantly decreased the tumor growth in the xenograft mice. Conclusion: The shZEB1-mediated down-regulation of the ZEB1 expression in the SKOV3 cells may be considered for future clinical trials.